Inflammasomes are activated in response to SARS-CoV-2 infection and are associated with COVID-19 severity in patients - Rodrigues, Tamara S.; de Sá, Keyla S.G.; Ishimoto, Adriene Y.; Becerra, Amanda; Oliveira, Samuel; Almeida, Leticia; Gonçalves, Augusto V.; Perucello, Debora B.; Andrade, Warrison A.; Castro, Ricardo; Veras, Flavio P.; Toller-Kawahisa, Juliana E.; et al. (The Journal of experimental medicine, 2021)
Severe cases of COVID-19 are characterized by a strong inflammatory process that may ultimately lead to organ failure and patient death. The NLRP3 inflammasome is a molecular platform that promotes inflammation via cleavage and activation of key inflammatory molecules including active caspase-1 (Casp1p20), IL-1β, and IL-18. Although participation of the inflammasome in COVID-19 has been highly speculated, the inflammasome activation and participation in the outcome of the disease are unknown. Here we demonstrate that the NLRP3 inflammasome is activated in response to SARS-CoV-2 infection and is active in COVID-19 patients. Studying moderate and severe COVID-19 patients, we found active NLRP3 inflammasome in PBMCs and tissues of postmortem patients upon autopsy. Inflammasome-derived products such as Casp1p20 and IL-18 in the sera correlated with the markers of COVID-19 severity, including IL-6 and LDH. Moreover, higher levels of IL-18 and Casp1p20 are associated with disease severity and poor clinical outcome. Our results suggest that inflammasomes participate in the pathophysiology of the disease, indicating that these platforms might be a marker of disease severity and a potential therapeutic target for COVID-19.